Estudio Comparativo de Herramientas Open Source para Soluciones de Inteligencia de Negocios y su posterior Aplicación Práctica para la Toma de Decisiones en la Empresa "Colbapi" de la Ciudad de Babahoyo - Benítez Córdova, Jean Carlos (2020)
The purpose of this case study is to know the type of transactions that are carried out at the Big Market Colbapi hardware store and the type of information that is generated to carry out a comparative analysis of the different existing business intelligence technologies. To achieve this purpose, the qualitative and comparative research methodology will be used to collect the information from different sources and proceed to learn about the different characteristics of each of the tools found. In order to meet these requirements, the present investigation raises the need to analyze Open Source tools for Business Intelligence in order to apply the selected tool in the company to provide key information to aid in the decision-making process.